2017
DOI: 10.1016/j.ecoser.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

A latent class analysis of public attitudes toward water resources with implications for recreational demand

Abstract: This study examines the extent to which heterogeneous environmental attitudes influence recreational demand in a river basin and the valuation of recreational benefits. We first employed a latent class analysis to reveal two distinct classes of respondents that differ in their environmental attitudes despite representing similar demographic characteristics. We then estimated a recreational demand model conditional on respondent's latent class membership after controlling for the probabilistic nature of the mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…A variety of studies have investigated differences in recreation preference among different groups (Boxall and Adamowicz, 2002;Scarpa and Thiene, 2004;Arnberger and Eder, 2011;Gentin, 2011;Juutinen et al, 2011;Ehrlich et al, 2017). Results include different age quartiles showing a difference in the importance placed on several site attributes (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of studies have investigated differences in recreation preference among different groups (Boxall and Adamowicz, 2002;Scarpa and Thiene, 2004;Arnberger and Eder, 2011;Gentin, 2011;Juutinen et al, 2011;Ehrlich et al, 2017). Results include different age quartiles showing a difference in the importance placed on several site attributes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Scarpa & Thiene (2004) found that climbers in the North-eastern Alps could be placed in four classes, using variables including environment severity, the difficulty of climbs and shelter availability. Ehrlich et al (2017) investigated recreational demand using perceptions towards water resource management in St. Johns River Basin in Florida (USA). They discovered two latent classes, both with similar demographic characteristics, though varying in attitudes and perceptions towards water management.…”
Section: Introductionmentioning
confidence: 99%
“…We employed a latent class analysis to categorize respondents with similar utility scores into segments. We used Bayesian Information Criterion (BIC) to select between models with 2, 3, 4, and 5 segments (Ehrlich et al ). The 5‐segment model outperformed the other models (5‐segment model BIC = 9,275.3; 4‐segment model resulted in second lowest score, BIC = 9,364.3).…”
Section: Methodsmentioning
confidence: 99%
“…The 5‐segment model outperformed the other models (5‐segment model BIC = 9,275.3; 4‐segment model resulted in second lowest score, BIC = 9,364.3). Following the latent class analysis, we treated segment membership as an independent variable (Boxall and Adamowicz ), allowing for the comparison of utility scores between segments (Ehrlich et al ). We also used segment membership to measure associations with bobwhite habitat management actions, values, and threat perceptions.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Ehrlich el al. [19] used the travel cost method to estimate the value of freshwater-based recreation in the St. Johns River Basin in Florida. On average, households in North and Central Florida were willing to pay $93.63 per trip per household.…”
Section: Related Economic Literaturementioning
confidence: 99%